Singing in South Africa: monitoring the occurrence of humpback whale (Megaptera novaeangliae) song near the Western Cape. Issue 2 (4th March 2021) - Ross-Marsh, E. C.; Elwen, S. H.; Prinsloo, A. S.; James, B. S.; Gridley, T.
ABSTRACT: Humpback whales ( Megaptera novaeangliae ) are highly vocal, producing a wide repertoire of sounds often organised into song. Song is prolific at breeding sites but also documented along migration routes and at feeding sites, including along the west coast of South Africa (28°–34°S). Here we examine the occurrence of humpback whale song within False Bay, South Africa, using intermittent recording periods from moored hydrophones spanning September 2016 to January 2018. Recordings from four locations were scrutinised for humpback whale vocalisations using long-term spectral averages (LTSAs). In total, 7205 h were examined, with song identified in 3% (211 h) of recording hours. Song was exclusively documented in September and October 2016 and was more prevalent at the most westerly sites. Diel patterns of song presence were modelled, showing the likelihood of detection was higher in the early morning and late evening (GAM: p < 0.05). On 15 occasions, two or more singers were detected with temporally overlapping song components. These results indicate prevalent, albeit seasonal, song production by humpback whales off the coast of South Africa and highlight the utility of passive acoustic monitoring to indicate their presence, behaviour, and potential population linkages in the region.